2020
DOI: 10.1128/aac.02429-19
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Ibrexafungerp (Formerly SCY-078), a First-in-Class Triterpenoid Inhibitor of (1→3)-β- d -Glucan Synthesis, and Isavuconazole for Treatment of Experimental Invasive Pulmonary Aspergillosis

Abstract: Ibrexafungerp (formerly SCY-078) is a semisynthetic triterpenoid and potent (1→3)-β-d-glucan synthase inhibitor. We investigated the in vitro activity, pharmacokinetics, and in vivo efficacy of ibrexafungerp (SCY) alone and in combination with antimold triazole isavuconazole (ISA) against invasive pulmonary aspergillosis (IPA). The combination of ibrexafungerp and isavuconazole in in vitro studies resulted in additive and synergistic interactions against Aspergillus spp. Plasma concentration-time curves of ibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
2
22
0
1
Order By: Relevance
“…While MIC 50 values for voriconazole were 2 mg/L by EUCAST and 0.5 mg/L by CLSI for the susceptible ones and 4 mg/L by both testing methodologies for the resistant strains, MEC 50 s for ibrexafungerp were 0.03 mg/L (EUCAST) and 0.06 mg/L (CLSI). These results are in agreement with those previously reported after in vitro testing [ 14 , 15 , 16 , 17 ] and after assessing in vivo activity when administered orally or intravenously in murine models of infection of invasive aspergillosis caused by A. fumigatus [ 20 , 22 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…While MIC 50 values for voriconazole were 2 mg/L by EUCAST and 0.5 mg/L by CLSI for the susceptible ones and 4 mg/L by both testing methodologies for the resistant strains, MEC 50 s for ibrexafungerp were 0.03 mg/L (EUCAST) and 0.06 mg/L (CLSI). These results are in agreement with those previously reported after in vitro testing [ 14 , 15 , 16 , 17 ] and after assessing in vivo activity when administered orally or intravenously in murine models of infection of invasive aspergillosis caused by A. fumigatus [ 20 , 22 ].…”
Section: Resultssupporting
confidence: 92%
“…However, ibrexafungerp has a longer half-life and is available as an oral formulation due to its improved pharmacokinetics and pharmacodynamics [ 35 ]. In addition to its good in vitro activity against susceptible and azole resistant Aspergillus spp., ibrexafungerp has proven to be effective against a caspofungin resistant A. fumigatus isolate [ 15 ] and has also yielded good results in neutropenic mice with invasive aspergillosis caused by azole susceptible and resistant A. fumigatus [ 20 , 22 ]. Therefore, this drug is currently undergoing phase II as an oral formulation for the treatment of invasive aspergillosis, as well as being in phase III for the treatment of vulvovaginal and invasive candidiasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies looking at the tissue distribution of ibrexafungerp achieved high concentrations in the skin, an attribute that may be of importance to limit C. auris skin colonization, with a potential impact of limiting transmission. Ibrexafungerp demonstrates activity across a range of invasive fungal diseases as a monotherapy but also in combination [ 58 , 59 ]. Early clinical evidence from an emergency-use Phase 3 study of ibrexafungerp for invasive candidiasis due to C. auris is promising.…”
Section: Discussionmentioning
confidence: 99%
“…Olorofim, a first-in-class orotomide inhibitor of dihydroorotate dehydrogenase in the pyrimidine salvage pathway, was studied in the rabbit model of acute IPA [ 69 ]. Using serum galactomannan as the primary pharmacodynamic endpoint, the authors found that C min and C min /MIC targets of 0.1 and 3.3, respectively, produced in vivo effects similar to those reported for isavuconazole administered in human exposures.…”
Section: Olorofimmentioning
confidence: 99%